The three-dimensional kinetic behaviour of the pelvic rotation in maximal sprint running - Sado, N.; Yoshioka, S.; Fukashiro, S. (Sports Biomechanics, 2017)
The purpose of this study was to investigate the effect of lumbosacral kinetics on sprinting. Twelve male sprinters performed 50 m sprints at maximal effort. Kinematic and ground reaction force data were recorded at approximately 40 m from sprint commencement. A whole-body inverse dynamics approach was applied to calculate joint forces and torques at the hip and lumbosacral joints. The contribution of the hips and lumbosacral joint torques to pelvic rotation was subsequently calculated, with joint force powers indicating the rate of mechanical energy transfer between segments across joint centres calculated for both hip joints. The kinetic analysis indicated that the lumbosacral torsional torque contributed significantly to pelvic rotation. Additionally, the pelvic rotation exerted anterior-posterior joint forces on the hips, contributing to the large positive joint force power at the hip of the stance leg. These hip joint force powers assisted in motion recovery during sprinting. In conclusion, the lumbosacral torsional torque might contribute to the recovery motion in sprinting through application of the anterior-posterior joint forces at the hip joints via pelvic rotation. ABSTRACT FROM AUTHOR